54.5k views
1 vote
8 g + 10 = 35 + 3 g

User Muirik
by
5.0k points

1 Answer

6 votes

Answer:

g = 5

Explanation:

8 g + 10 = 35 + 3 g

in order to get the value of g, firt of all rearrange the expression or in ither words collect the like terms.

8 g + 10 = 35 + 3 g

8g + 10 - 3g = 35

NOTE; when you are moving a number with positive sign across the equal to = sign the positive changes to negative and same thing applies to the negative sign it changes to positive sign.

we have;

8g -3g = 35 - 10

5g = 25

divide both sides by 5

5g/5 = 25/5

g = 5

User Pedromendessk
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.